Redox-dependent activation of CO dehydrogenase from Rhodospirillum rubrum - Heo, Jongyun (The National Academy of Sciences, 2001)
Studies of initial activities of carbon monoxide dehydrogenase (CODH) from Rhodospirillum rubrum show that CODH is mostly inactive at redox potentials higher than −300 mV. Initial activities measured at a wide range of redox potentials (0–500 mV) fit a function corresponding to the Nernst equation with a midpoint potential of −316 mV. Previously, extensive EPR studies of CODH have suggested that CODH has three distinct redox states: (i) a spin-coupled state at −60 to −300 mV that gives rise to an EPR signal termed C(red1); (ii) uncoupled states at <−320 mV in the absence of CO(2) referred to as C(unc); and (iii) another spin-coupled state at <−320 mV in the presence of CO(2) that gives rise to an EPR signal termed C(red2B). Because there is no initial CODH activity at potentials that give rise to C(red1), the state (C(red1)) is not involved in the catalytic mechanism of this enzyme. At potentials more positive than −380 mV, CODH recovers its full activity over time when incubated with CO. This reductant-dependent conversion of CODH from an inactive to an active form is referred to hereafter as “autocatalysis.” Analyses of the autocatalytic activation process of CODH suggest that the autocatalysis is initiated by a small fraction of activated CODH; the small fraction of active CODH catalyzes CO oxidation and consequently lowers the redox potential of the assay system. This process is accelerated with time because of accumulation of the active enzyme.